Частная собственность сквозь призму социологического институционализма - Резник, В. (Социология: теория, методы, маркетинг, 2005)
The author of this article makes an attempt to define the categorical matter of conceptual model of social institution. Thereto the institutional conceptualizations lately suggested by Ukrainian sociologists are used as initial patterns. The named categorical pattern will be applied in the future as a means to define theoretical and methodological basis for the analysis of integration/disintegration processes in the social structure of modern Ukrainian society that changed owing to the private property re-institutionalization in the course of privatization.